The Relationship between Parental Social Support with Achievement Motivation in Senior High School Students: Hubungan antara Dukungan Sosial Orang Tua dengan Motivasi Berprestasi pada Siswa Sekolah Menengah Atas - Pradnya Ayu Paramita; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by a decrease in achievement motivation in Al-Islam Krian High School students. The purpose of this study is to find out and provide an explanation of the relationship between parental social support and achievement motivation in Al-Islam Krian High School students. This research method is quantitative correlation with the subjects of SMA Al-Islam Krian, totaling 269 students. Determination of subjects using proportional sampling technique, namely the determination of samples to take representatives from each group in the population whose number is adjusted to the number of subject members in each group. The variables in this study were parental social support and achievement motivation. The data collection in this study used a psychological preparation scale, namely the Likert scale for the variables of parental social support and achievement motivation. Analysis of the data in this study using SPSS 26.0 for Windows. The results of data analysis showed that there was a positive relationship between parental social support and achievement motivation with an rxy value of 0.517, a significance of 0.000. Highlights: Parental social support positively influences achievement motivation in Al-Islam Krian High School students. The research method employed is quantitative correlation, using a proportional sampling technique. Data analysis was conducted using SPSS 26.0 for Windows, revealing a significant positive relationship (rxy = 0.517, p = 0.000) between parental social support and achievement motivation. Keywords: achievement motivation, parental social support, Al-Islam Krian High School, quantitative correlation, Likert scale